The call for Islamization for modern psychology - Abdul Razak, Mohd. Abbas; Rahath House, Yousef (2017)
This presentation on ‘The Call for Islamization of Modern Psychology’ elucidates the nature and focus of psychology in the West and Muslim world. Since the West has gone through a period of shifting of paradigms in its views on man and psychology, and the fact that there exist a myriad of schools in psychology, the presenters would like to restrict their scope of analysis to only three schools from the western mainstream psychology. Among others that include psychoanalysis, behaviorism, and humanistic psychology. In a contrastive manner ideas on Man from the three schools will be compared with what has been conceptualized in Islamic psychology. Due to the fact that at times western schools of psychology agree and complement one another in matters related to man and at other times they are at loggerhead with one another, has created an opportunity for the introduction of Islamic psychology. It is the conviction of the presenters that Islamic ideas on man which are comprehensive and all-encompassing can act as a ‘peace-maker’ to the polemical issues that are prevalent in western schools of psychology. It is believed that ideas provided by Islamic psychology can harmonize many of the differences found in western mainstream psychology